Efektivitas Ekstrak Metanol Daun Sembung Rambat (Mikania micrantha Kunth) Terhadap Pertumbuhan Jamur Candida albicans - Masnur Turnip, Raniyanti Rieska Alfiah, Siti Khotimah, (Universitas Tanjungpura, 2015)
Candida albicans is a fungus which commonly found in the human body and can cause candidiasis disease with varies symptoms. One of the potential anti fungal plant is Mikania micrantha Kunth leaves. The purpose of this study was to determine the ability of M. micrantha fungus. The anti fungal activity tests on M. micrantha leaves were conducted by using Kirby-Bauer smear method. The test were carried out with 7 treatments, ie : negative control, solvent control (DMSO 10%), posiive control (ketokonazole 2%), concentrate of M. micrantha leaves extract as much as 20%, 25%, 30%, 35% and 40%. From the result on 30% anti fungal concetration, it showed that the activity level was very strong. This case shows that 30% concentrate of M. micrantha leaves extract is the most potential concentrate to inhibit the growth of C.albicans fungus.